KOMUNIKASI POLITIK DEWAN PERWAKILAN RAKYAT DAERAH KOTA PEKANBARU DALAM MENJALANKAN FUNGSI LEGISLASI TAHUN 2014-2019 - Firman Andika; Tito Handoko; Belli Nasution; Syafri Harto (Jurnal Ranah Komunikasi, 2021)
This study aims to identify, explain and describe the Political Communication of the Regional Representative Council of Pekanbaru City in Carrying Out the Legislation Function in 2014-2019. This research uses descriptive qualitative research methods. Determination of informants from this study using purposive informant selection technique, while the object of this research is the Political Communication of the Regional Representative Council of Pekanbaru City in Carrying Out the Legislation Function. The data collection techniques used were in-depth interviews, observation and documentation. In achieving the validity of the data in this study, participation extension and triangulation were used. The first research results, political communicators in carrying out the legislative functions of the Pekanbaru City DPRD in 2014-2019 were only carried out by members of the Pekanbaru City DPRD during a recess which was carried out in their electoral area. The Regional Regulation Formation Agency should have played a very large role in carrying out its legislative function because it could directly receive and convey information related to the Draft Regional Regulation which is still in the process of being discussed with the Pekanbaru City Government. Second, the message in carrying out the legislative function of the Pekanbaru City DPRD in 2014-2019 has not been implemented effectively, the two-way communication between the Pekanbaru City DPRD and the community has not been maximal. There are still people who do not know the information related to the Draft Regional Regulation that is being discussed and the lack of public information regarding the Regional Regulation that has been passed. Third, the media used in carrying out the legislative function of the Pekanbaru City DPRD uses printed media, namely newspapers, but it is still not running optimally as well as social media managed by the Pekanbaru City DPRD such as Instagram, Facebook and Twitter. Social media has not maximally published activities related to the implementation of the legislative function. Fourth, the target audience in carrying out the legislative function is the people of Pekanbaru City. However, the legislative function is still not very effective because the public is not very enthusiastic about the activities carried out by the Pekanbaru City DPRD.